PENGEMBANGAN Ã¢â‚¬Å“TECHNOPRENEURSHIPÃ¢â‚¬Â DI PERGURUAN TINGGI DAN IMPLIKASI KEBIJAKANNYA - hamid, hamid (Badan Pengkajian dan Penerapan Teknologi, 2011)
In dealing with labor issues, it needs continued effort to reduce unemployment breakthrough that is felt over the yearscontinued to to increase , particularly from college graduates. Providing subject matter Technopreneurship expected to provide an alternative solution, especially in view of the changing pattern (mindset) of student job seekers into job creators. Technopreneuship load theory and practice of entrepreneurship by providing innovation through the application of technology which are held by the college in particular and other technology resources to create innovative products so as to generate new technology-based entrepreneurs. To make that happen, it is necessary to know the conditions and constraints of the college in the development of this Technopreneurship. Because certainly at this moment the new universities provide an introduction to entrepreneurship has not been in the form of technology entrepreneurship. For that team BPP Technology has conducted a study to provide advice to the parties involved in the development of good Technopreneurship related to the condition, model development and the policies required to encourage the development of Technopreneurship in college.